An adaptive control system for a shell-and-tube heat exchanger - Skorospeshkin M. V. Maksim Vladimirovich; Sukhodoev M. S. Mikhail Sergeevich; Skorospeshkin V. N. Vladimir Nikolaevich; Rymashevskiy P. O. (2017, 2017)
Title screen